Evaluating a scalable ARCHES (Addressing Reproductive Coercion in Health Settings) model in government health facilities in Uasin Gishu county, Kenya: study protocol for a cluster-randomized controlled trial - Erin Pearson; Jasmine Uysal; Jamie Menzel; Chi-Chi Undie; George Odwe; Wilson Liambila; Jay G. Silverman (BMC, 2023)
Abstract Background Since 2013, the World Health Organization has recommended that reproductive coercion (RC) and intimate partner violence (IPV) be addressed within reproductive health services and, in 2018, the Lancet Commission on Sexual and Reproductive Health and Rights found that RC and IPV were significant contributors to unmet need for family planning (FP) and unintended pregnancy. In Kenya, the Ministry of Health (MOH) has made reduction of unintended pregnancy and gender-based violence a primary objective. Despite this need and guidance, no clinic-based intervention models outside of the U.S. (apart from the one described here) have demonstrated efficacy to improve FP use and reduce IPV or RC thereby reducing unintended pregnancy. ARCHES (Addressing Reproductive Coercion in Health Settings) is a brief, clinic-based intervention delivered by existing FP providers aiming to: (1) Increase women's ability to use FP without interference, (2) Provide a safe and supportive environment for IPV disclosure and referral to support services, and (3) Improve quality of FP counseling, including addressing RC and IPV. The objective of this study is to generate evidence on scaling integrated FP services (including FP, RC, and IPV) in public sector health facilities in Uasin Gishu county, Kenya via adaptation and implementation of ARCHES in partnership with the Kenya MOH. Methods A cluster-randomized controlled trial paired with concurrent implementation science assessments will test effectiveness of the ARCHES model, adapted for scale by the Kenya MOH, in reducing unintended pregnancy. Female FP clients aged 15-49 years at selected sites will complete baseline surveys (immediately prior to receiving care), immediately post-visit exit surveys, and 6-month follow-up surveys. Provider surveys will assess changes in gender-equitable attitudes and self-efficacy to address violence reported by their clients. Costs associated with scaling ARCHES will be tracked and utilized in combination with results of the effectiveness trial to assess costs and cost-effectiveness relative to the standard of care. Discussion This study will provide evidence of the effectiveness of a facility-based intervention to address RC and IPV within public sector FP services at scale, as adapted and implemented in Uasin Gishu county, Kenya. Trial registration Trial registered on 28 September 2023 with clinicaltrials.gov NCT06059196.